Repetitive Transcranial Magnetic Stimulation in Managing Mild Traumatic Brain Injury‐Related Headaches. Issue 2 (10th November 2015) - Leung, Albert; Shukla, Shivshil; Fallah, Amir; Song, David; Lin, Lisa; Golshan, Shahrokh; Tsai, Alice; Jak, Amy; Polston, Greg; Lee, Roland
Abstract : Objective: Headache is one of the most common debilitating chronic pain conditions in either active or retired military personnel with mild traumatic brain injury (MTBI). This study assessed the effect of repetitive transcranial magnetic stimulation (rTMS) in alleviating MTBI‐related headache (MTBI‐HA). Materials and Method: Veterans with MTBI‐HA were randomized to receive either real rTMS (REAL group) at 10 hz for a total of 2000 pulses divided into 20 trains with one‐sec inter‐train interval or sham rTMS (SHAM group) at the left motor cortex (LMC) with brain magnetic resonance imaging neuronavigation guidance. Pretreatment, posttreatment one‐week and four‐week headache and neuropsychological assessments were conducted. Result: Thirty veterans were screened and twenty four (21 men and 3 women with average year‐old ± SD at 14.3 ± 12.6) subjects' data were analyzed. A two‐factor (visit × treatment) repeated measures analysis of variance (RM‐ANOVA) indicated a close to significant ( p = 0.06) trend of interaction between pretreatment and posttreatment one‐week assessment with the intensity of the persistent daily headache decreasing from 5.7 ± 1.9 to 2.2 ± 2.7 and 4.6 ± 1.3 to 3.5 ± 2.0 for the REAL and SHAM groups, respectively. Subsequent analyses indicated REAL group demonstrated a significantly ( p = 0.041) higher % of reduction in persistent headache intensity than the SHAM group (56.3 ± 48.2% vs.15.4 ± 43.6%) at the posttreatment one‐week assessment and the trend continued to the four‐week assessment. Overall, a significantly ( p = 0.035) higher percentage of the subjects in the REAL group (58.3%) demonstrated at least a 50% headache intensity reduction at posttreatment one‐week assessment compared with the SHAM group (16.6%). The overall composite score of functionally debilitating headache exacerbation is significantly ( p = 0.017) reduced in REAL group at the posttreatment four‐week assessment in comparison with the SHAM group. No major sustained change in neuropsychological assessments was noted. Conclusion: The studied rTMS protocol appears to be a clinically feasible and effective treatment option in managing MTBI‐HA.